Infant and young child feeding practices in two provinces of Afghanistan: results from two rounds of large country-lot quality assurance sampling surveys - Shinwari, Ibrahim; Aminee, Ahmad Wali; Warvadekar, Kirti; Gupta, Payal; Chaudhery, Deepika Nayar; Raut, Manoj Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: As per NNS 2013, about 58% of the infants aged 0-5 months were exclusively breastfed. The data also shows that only 41% infants 6-8 months of age were introduced solid, semi-solid and soft foods. Further only 28% of children aged 6-23 months received foods from four or more food groups during last 24 hours preceding the survey. Suboptimal IYCF practices are therefore considered to be an important contributor to the high rates of under nutrition in Afghanistan. The program monitoring at two time points was conducted to inform the program about the current status of the program activities and any course correction required. It was also meant to inform the government and other stakeholders on the feasibility of program strategies in improving IYCF practices and recommendations for scale-up programs. Methods: The program monitoring was performed before and after the (IYCN) program roll out in Wardak and Laghman provinces of Afghanistan. To understand and monitor the status of process and program indicators, a Large Country-Lot Quality Assurance Sampling (LC-LQAS) study design was adopted. Results: Minimum acceptable diet was observed to be 54% (95% CI: 46%, 61%) in the second round, which was 44% (95% CI: 35%, 53%) in the first round. Conclusions: Minimum acceptable diet among the children of age group 6-23 months was found to be consistently doing well in both the rounds. LC-LQAS was found to be an apt method to estimate the IYCN indicators at time points with low resource use.